SAT0073 Theranostic approach in arthritis: A feasibility study in rats. (23rd January 2014) - Welker, P.; Licha, K.; Gemeinhardt, I.; Bahner, M.; Berger, J.; Mangoldt, D.; Schnorr, J.; Schirner, M.
Abstract : Background: Assessment of arthritis using fluorescence optical imaging (FOI) in combination with the fluorophore indocyanine green (ICG) is now clinically established [1]. Beyond imaging of inflammation, FOI also provides the opportunity to monitor drug targeting of biological therapeutics into inflamed joints. Quantitative information of drug targeting would allow for patient selection and individual treatment schedules. Objectives: We report the first synthesis of etanercept-ICG-conjugates and the quantitative monitoring of drug targeting into inflamed joints of collagen II induced arthritis using a modified fluorescent camera system (Xiralite). Methods: Inflammatory arthritis was induced by twice injections of bovine collagen II (day 0, day 7) in female Lewis rats. Rats were monitored for joint swelling, pain, redness and mobility (score 0 to 3). The TNFa binding protein etanercept (Enbrel®, Pfizer) was chemically conjugated with an ICG derivative suited for labeling of proteins. The etanercept-6S-ICG (Eta-6S-ICG) conjugate was photophysically characterized and tested for binding affinity The fluorescence camera system Xiralite (mivenion GmbH, Germany) [1] was modified to enable imaging of rats. On day 14 after first injection of collagen, Eta-6S-ICG (n=6), IgG-6S-ICG (n=3), or the inflammation-targeted macromolecule polyglycerolsulfate-6S-ICG (dPGS-6S-ICG, n=5) [2] were s.c. or i.v. injected in a dose of 10 nMol/kg b.w. Fluorescence measurement was performed before and 1 h, 3 h, 24 h and 48 h after injection. Fluorescence intensity (FI) was measured in ROI over the tibio-tarsal and interphalangeal articulations and compared with healthy reference ROI. In addition, targeting was studied in rat tissues 3 or 24 h post injection of Eta-6S-, IgG-6S- or dPGS-6S-indocarbocyanine conjugates using fluorescence histology. Results: Binding affinity of etanercept was not attenuated by chemical conjugation with 6S-ICG. Eta-6S-ICG exerts high fluorescence quantum yield compared with ICG. FI was detected already 24 hours after administration of Eta-6S-ICG and further increased until 48 hours after injection. Significant FI at 48 hours after injection of Eta-6S-ICG was measured in tibio-tarsal joints (score 1: 15.8±2.9; score 3: 31.0±4.6) while FI in interphalangeal joints was low (score 1: 6.3±1.0; score 3: 7.7±1.2). In contrast, dPGS-6S-ICG exhibited high FI in both tibio-tarsal joints (score 1: 23.5±4.9; score 3: 69.8±17.5) and interphalangeal joints (score 1: 20.9±5.8; score 3: 37.0±4.7). Both Eta-6S- ICG and dPGS-6S-ICG show strong targeting to inflamed synovial tissue and cartilage compared with IgG-6S-ICG. Conclusions: FOI and labeling of macromolecular therapeutics with novel ICG derivatives provide a novel rationale for sensitive and quantitative monitoring of arthritis therapy. Further studies have to determine the effect of varying molecular size on the degree of targeting of inflamed joints. References: Werner S et al. Inflammation assessment in patients with arthritis using a novel in vivo fluorescence optical imaging technology. Ann Rheum Dis doi:10.1136/ard.2010.148288. Licha K et al. Fluorescence imaging with multifunctional polyglycerol sulfates: novel polymeric near-IR probes targeting inflammation. Bioconjug Chem; doi:10.1021/bc2002727 Disclosure of Interest: P. Welker Employee of: mivenion GmbH, K. Licha Shareholder of: mivenion GmbH, I. Gemeinhardt: None Declared, M. Bahner Shareholder of: mivenion GmbH, J. Berger Employee of: mivenion GmbH, D. Mangoldt Employee of: mivenion GmbH, J. Schnorr: None Declared, M. Schirner Shareholder of: mivenion GmbH